Application of the Cooperative Learning Model using the Jigsaw type to improve Student Learning Outcomes at SMA Negeri Ambulu - Khoirul Anwar; Laily Ramadhanty (LPPM Institut Studi Islam Sunan Doe, 2023)
Based on research on the application of the cooperative learning model with the jigsaw type of grade X-6 students of SMA Negeri Ambulu on the topic environmental pollution, the results obtained consisted of three cycles, namely cycle I, cycle II, and cycle III. This research is a classroom action research that aims to determine the improvement of students in solving problems in the form of student success in the value of the cognitive aspect and the value of the affective aspect. In cycle I, the results were obtained on the cognitive and affective aspects, each with an average value of 62.5 and 67.25. Whereas in cycle II the results were obtained on the cognitive and affective aspects with an average value of 66.67 and 70.67, respectively. While in cycle III the results were obtained on the cognitive and affective aspects with an average value of 75.32 and 77.32, respectively. So it can be concluded that in each learning cycle there is an increase in learning outcomes and the application of the jigsaw cooperative learning model can run effectively and optimally.